Correlation between cholesterol and ambulatory blood pressure in postmenopausal osteoporotic patients: a post-hoc analysis of an observational study - Lin, Zebin; Wu, Tianlong; Zhao, Yipin; Wang, Chizhen; Wu, Gaofeng (Frontiers in Medicine, 2025)
ObjectiveTo explore the correlation between cholesterol levels and 24-h dynamic blood pressure in postmenopausal women with osteoporosis.MethodsAmbulatory blood pressure monitoring was performed using a portable automated device, and cholesterol levels were measured using a fully automated biochemical analyzer. The relationship between cholesterol and blood pressure was analyzed using Shepherd’s Pi correlation and generalized additive models (GAM) with piecewise linear regression to identify threshold effects.ResultsThe mean age of the participants was 73 years. Shepherd’s Pi correlation analysis revealed a negative correlation between total cholesterol (TC) and intact parathyroid hormone (iPTH), as well as between high-density lipoprotein cholesterol (HDL-C) and β-crosslaps. Using GAM and piecewise linear regression to identify threshold effects, we found that when TC was ≥5.5 mmol/L, it was significantly and positively associated with 24-h mean systolic blood pressure (SBP) (β = 12.62, 95% CI: 5.23–20.00, p < 0.001), as well as with diurnal and nocturnal mean SBP. Similarly, low-density lipoprotein cholesterol (LDL-C) ≥ 3.9 mmol/L showed a positive correlation with multiple blood pressure parameters, including 24-mSBP (β = 18.33, 95% CI: 5.93–30.74, p = 0.004), diastolic blood pressure (DBP), and both diurnal and nocturnal measurements. No significant associations were observed below these threshold values. In contrast, HDL-C < 1 mmol/L was negatively correlated with 24-mSBP (β = −32.13, 95% CI: −57.67 to −6.60, p = 0.014), but not with DBP.ConclusionA threshold effect exists between cholesterol and blood pressure in postmenopausal osteoporosis patients. Elevated TC and LDL-C beyond specific thresholds, as well as low HDL-C, are associated with higher blood pressure levels.